PEMBERDAYAAN LEMBAGA PEMERINTAHAN NAGARI MELALUI PENDEKATAN BALANCED SCORECARD - Maani, Karjuni Dt. (Jurnal Demokrasi, 2008)
This article tries to describe the approach of ‘balanced scorecard’ in Nagari government in West Sumatera. The approach of balanced scorecard is very relevant to adopt in arranging the istitution of Nagari government. This approach offered the balance of four perspective: implementation of internal process of Nagari government,  organization learning for development according to current situation, delivery of good service toward society, and enhancement of monetary performance of Nagari through natural resources of the Nagari. Kata Kunci: Pemberdayaan, pemerintahan nagari, balanced scocard